TNF 41-62 and TNF 78-96 Have Distinct Effects on LPS-induced Tissue Factor Activity and the Production of Cytokines in Human Blood Cells - Eliassen, L.T.; Rekda, Ø.; Svendsen, J.S.; Østerud, B. (Thrombosis and Haemostasis, 2000)
Biological activities of peptides representing two different regions in the TNF molecule were investigated. We have earlier reported that one of the peptides studied, TNF 36-62, induced chemotaxis in granulocytes and monocytes. TNF 41-62, a shorter analog of TNF 36-62, possessed similar chemotactic effects. Both peptides caused a weak enhancement of LPS -induced IL-6 production and tissue factor activity by monocytes in whole blood. The third peptide studied, TNF 78-96, was selected from a region located on the opposite side of the β-sheet sandwich structure of the TNF molecule, and includes the loop 84-88 that has been shown to be involved in TNF receptor interaction. TNF 78-96 possessed properties quite different from TNF 36-62 and TNF 41-62. It amplified several fold PMA-induced secretion of elastase, and enhanced significantly PMA-induced secretion of cathepsin G from the neutrophils, activities which were effectively abolished by an anti-human TNF antibody. The TNF 78-96 peptide also inhibited LPS-induced TF activity in monocytes of whole blood, and it abolished the TNF enhancing effect of LPS-induced TF activty in a dose dependent manner. This suggests that the TNF 78-96 peptide may bind to the TNF receptor(s), without potentiating the same signals as native TNF. It may thereby prevent binding of the native TNF and the resultant activation effect of TNF. It also, at high concentrations, inhibited LPS-induced IL-6 production whereas it caused a doubling of LPS-induced IL-8 in monocytes and granulocytes in whole blood. These results clearly show that distinct TNF activities can be induced by peptide sequences taken from different regions of TNF. The TNF 78-96 peptide might be useful in downregulation of LPS-induced monocyte activations in vivo.
Keywords: Molecular modelling; TNF peptides; leukocytes; tissue factor